Groundwater pollutants characterization by geochemometric technique and geochemical modeling in tropical savanna watershed - Mohammed, Adamu Usman; Aris, Ahmad Zaharin; Ramli, Mohammad Firuz; Mohd Isa, Noorain; Arabi, Abdullahi Suleiman; Jabbo, Josiah Nuhu (Springer Science and Business Media B.V., 2023)
Multiple interactions of geogenic and anthropogenic activities can trigger groundwater pollution in the tropical savanna watershed. These interactions and resultant contamination have been studied using applied geochemical modeling, conventional hydrochemical plots, and multivariate geochemometric methods, and the results are presented in this paper. The high alkalinity values recorded for the studied groundwater samples might emanate from the leaching of carbonate soil derived from limestone coupled with low rainfall and high temperature in the area. The principal component analysis (PCA) unveils three components with an eigenvalue > 1 and a total dataset variance of 67.37%; this implies that the temporary hardness of the groundwater and water–rock interaction with evaporite minerals (gypsum, halite, calcite, and trona) is the dominant factor affecting groundwater geochemistry. Likewise, the PCA revealed anthropogenic contamination by discharging SO42-,NO3-,Cl- and K + from agricultural activities and probable sewage leakages. Hierarchical cluster analysis (HCA) also revealed three clusters; cluster I reflects the dissolution of gypsum and halite with a high elevated load of NO3- released by anthropogenic activities. However, cluster II exhibited high KHCO32- and KCl- loading in the groundwater from weathering of bicarbonate and sylvite minerals. Sulfate (SO42-) dominated cluster III mineralogy resulting from weathering of anhydrite. The three clusters in the Maiganga watershed indicated anhydrite, gypsum, and halite undersaturation. These results suggest that combined anthropogenic and natural processes in the study area are linked with saturation indexes that regulate the modification of groundwater quality.